Development of Game-BasedLearning Digital Modules in Class IV MI Datok Sulaiman Palopo - Misdawati; Baderiah; Firman (South Sulawesi Education Development (SSED), 2023)
In today's digital era, innovation and creativity in education are important. This research develops a game-based learning digital module for material work at MI Datok Sulaiman, Palopo City. The ADDIE method is used in development with four stages: analysis, design, development, and implementation. Data was collected through observation, interviews, questionnaires and documentation analysed qualitatively and quantitatively. The needs analysis results show that teachers and students need clear, detailed, colourful, and pictorial digital modules. Product validation by expert validators gives very valid results (94.87%), and the practicality of the module is also very practical (84.79%). This module is feasible and practical to use in learning.